PENGUNGKAPAN TERKAIT SDGs DAN PROFITABILITAS SERTA ANALISIS INDUSTRI - Siti Alfiah; Regina Jansen Arsjah (LEMBAGA PENERBIT FAKULTAS EKONOMI DAN BISNIS UNIVERSITAS TRISAKTI, 2021)
This research was conducted to capture the extent to which Indonesian companies have revealed their activities related to each goal of the Sustainabls Development Goals (SDGs), specifically in the year the SDGs were launched. Aim of the study is to analyze and obtain empirical evidence about the effect of SDGs’ related company disclosure, firm size, leverage on profitability, and related industrial analysis. The SDGs’ related company disclosure was measured using content analysis. This research conducted on all companies listed on the Indonesia Stock Exchange (IDX) in 2015, with a sample, amounted to 468 companies. The results show the positive effect of SDGs’ related company disclosure on profitability and the negative effect of leverage on profitability. There is no effect of size on profitability. The results also show that the financial sector revealed the most SDGs, followed by the basic industry and chemical sector, property, and real estate sector, and the consumer goods sector.